Criminal Policy on Narcotics Crimes in Maluku as an Archipelago Province - Suhardiman, Suhardiman; Toule, Elsa Rina Maya; Taufik, Iqbal (PAMALI: Pattimura Magister Law Review, 2026)
Introduction: Maluku Province, as an archipelagic region, is highly vulnerable to narcotics trafficking and abuse. Its strategic yet remote location makes it a potential route for illicit drug distribution. The growing spread of narcotics poses a serious threat to youth and legal order, requiring comprehensive and contextual criminal policy responses.Purposes of the Research: This study aims to analyze the criminal policy in addressing narcotics crimes in Maluku Province and to identify the influencing factors.Methods of the Research: The research applies both normative and empirical juridical methods. Data were collected through document analysis of laws and legal literature, as well as interviews with law enforcement authorities and related agencies in the region.Results Main Findings of the Research: The findings reveal that current criminal policies in Maluku face substantial challenges, including limited infrastructure, lack of qualified personnel, and weak inter-agency coordination. The archipelagic geography itself emerges as a significant barrier to effective law enforcement. This study offers a novel contribution by mapping these island-based structural constraints and proposing an integrated criminal policy model that combines penal and non-penal approaches—such as legal education, community empowerment, and rehabilitation. This framework holds potential for broader application in other archipelagic or remote regions of Indonesia.